Broad Detection of Alterations Predicted to Confer Lack of Benefit From EGFR Antibodies or Sensitivity to Targeted Therapy in Advanced Colorectal Cancer. (28th September 2016) - Rankin, Andrew; Klempner, Samuel J.; Erlich, Rachel; Sun, James X.; Grothey, Axel; Fakih, Marwan; George, Thomas J.; Lee, Jeeyun; Ross, Jeffrey S.; Stephens, Philip J.; Miller, Vincent A.; Ali, Siraj M.; et al.
Abstract : Introduction: A KRAS mutation represented the first genomic biomarker to predict lack of benefit from anti-epidermal growth factor receptor (EGFR) antibody therapy in advanced colorectal cancer (CRC). Expanded RAS testing has further refined the treatment approach, but understanding of genomic alterations underlying primary and acquired resistance is limited and further study is needed. Materials and Methods: We prospectively analyzed 4, 422 clinical samples from patients with advanced CRC, using hybrid-capture based comprehensive genomic profiling (CGP) at the request of the individual treating physicians. Comparison with prior molecular testing results, when available, was performed to assess concordance. Results: We identified a RAS/RAF pathway mutation or amplification in 62% of cases, including samples harboring KRAS mutations outside of the codon 12/13 hotspot region in 6.4% of cases. Among cases with KRAS non-codon 12/13 alterations for which prior test results were available, 79 of 90 (88%) were not identified by focused testing. Of 1, 644 RAS/RAF wild-type cases analyzed by CGP, 31% harbored a genomic alteration (GA) associated with resistance to anti-EGFR therapy in advanced CRC including mutations in PIK3CA, PTEN, EGFR, and ERBB2 . We also identified other targetable GA, including novel kinase fusions, receptor tyrosine kinase amplification, activating point mutations, as well as microsatellite instability. Conclusion: Extended genomic profiling reliably detects alterations associated with lack of benefit to anti-EGFR therapy in advanced CRC, while simultaneously identifying alterations potentially important in guiding treatment. The use of CGP during the course of clinical care allows for the refined selection of appropriate targeted therapies and clinical trials, increasing the chance of clinical benefit and avoiding therapeutic futility. Abstract : Comprehensive genomic profiling (CGP) reliably detects alterations associated with a lack of benefit to anti-epidermal growth factor receptor therapy in advanced colorectal cancer, while simultaneously identifying alterations that are potentially important in guiding treatment. This study found that the use of CGP during the course of clinical care allows for the refined selection of appropriate targeted therapies and clinical trials, increasing the chance of clinical benefit and avoiding therapeutic futility.